Gobierno institucional de la ética de la investigación: el problema de la autonomía revisitado desde las tensiones de un modelo de supervisión centralizado y multidisciplinar (2014)
Based on a study case drawn from meetings of a Research Ethics Committee - REC, in this thesis I analyze the dynamics of what is known as the institutional surveillance model of research ethics. In order to elucidate the institutional and interactional dimensions of the committee, I use the concept of “boundary organizations.” This concept allows me to: first, discuss how the committee negotiates within what I describe as the institutional network of research ethics governance, a negotiation that results from tensions among actors located within the network. And second, to deeply analyze the difficulties generated by the conjunction of “communities of practice,” and the strategies used to solve those difficulties. In despite of having regulatory expectations, by enacting a discourse that preserved the confidence in researchers’ moral behavior, and by using internal procedures concentrating ethical assessment in the head of health experts trained in bioethics, I conclude that the Committee consolidated as a space in which researchers deepened their functional and institutional autonomy.